(untitled) (Global Journal of Management and Business Research, 2023)
The empirical literature is bounded to explaining the use of emerging regulatory innovation in designing meta-regulation under risk-based regulatory strategy as a new regulatory mix Therefore this paper aims to demonstrate how enterprise risk management ERM an emergent regulatory innovation uses to design meta-regulation under the risk-based strategy Based on qualitative content analysis of a central bank s annual report in an emerging economy over eleven years including the issued guidelines and circulars this paper reveals the dimension of ERM as a meta-regulatory toolkit in the regulatory regime